Increased population exposure to extreme droughts in Iberia due to 0.5 °C additional anthropogenic warming - Ana Russo; Virgílio A Bento; Andreia F S Ribeiro; Daniela C A Lima; João A M Careto; Pedro M M Soares; Renata Libonati; Ricardo M Trigo; Célia M Gouveia (Environmental Research Letters)
This study investigates the effects of incremental global warming, specifically the transition from 1.5 °C to 2.0 °C, on drought conditions in the Iberian Peninsula (IP). Our findings confirm a substantial increase in the frequency and intensity of droughts in the IP due to anthropogenic climate change. We highlight the importance of temperature in drought representation and underscore the urgent need to limit global warming below 1.5 °C, in line with international climate policies. The analysis reveals that the exacerbation of drought conditions is more pronounced under higher emission scenarios, particularly RCP8.5, emphasizing the critical role of emission reduction in climate change mitigation. Furthermore, a substantial increase in affected land area and population exposure to drought is observed, especially under the higher-emission scenario. Climate change emerges as the primary factor contributing to increased drought exposure, with emission reduction efforts offering potential mitigation. To overcome limitations associated with model uncertainties, a multi-model multi-variable ensemble approach was employed to enhance the regional specificity of the findings. This provides valuable insights for local climate adaptation and mitigation strategies. Results suggest that mitigating anthropogenic warming by 0.5 °C to achieve the 1.5 °C warmer climate rather than 2.0 °C may provide benefits for future drought risks and impacts in the IP and underscore the urgency of implementing stringent climate policies. By offering a comprehensive assessment of drought conditions and population exposure, this study informs decision-making and climate resilience strategies, emphasizing the need for immediate action to mitigate adverse impacts on ecosystems and human populations.